The Unexpected Effects of Beneficial and Adverse Social Experiences during Adolescence on Anxiety and Aggression and Their Modulation by Genotype - Meyer, Neele; Richter, S. Helene; Schreiber, Rebecca S.; Kloke, Vanessa; Kaiser, Sylvia; Lesch, Klaus-Peter; Sachser, Norbert (Frontiers in Behavioral Neuroscience, 2016)
Anxiety and aggression are part of the behavioral repertoire of humans and animals. However, in their exaggerated form both can become maladaptive and result in psychiatric disorders. On the one hand, genetic predisposition has been shown to play a crucial modulatory role in anxiety and aggression. On the other hand, social experiences have been implicated in the modulation of these traits. However, so far, mainly experiences in early life phases have been considered crucial for shaping anxiety-like and aggressive behavior while the phase of adolescence has mainly been neglected. Therefore, the aim of the present study was to elucidate how levels of anxiety-like and aggressive behavior are shaped by social experiences during adolescence and serotonin transporter (5-HTT) genotype. For this purpose, male mice of a 5-HTT knockout mouse model including all three genotypes (wildtype, heterozygous and homozygous 5-HTT knockout mice) were either exposed to an adverse social situation or a beneficial social environment during adolescence. This was accomplished in a custom-made cage system where mice experiencing the adverse environment were repeatedly introduced to the territory of a dominant opponent but had the possibility to escape to a refuge cage. Mice encountering beneficial social conditions had free access to a female mating partner. Afterwards, anxiety-like and aggressive behavior was assessed in a battery of tests. Surprisingly, unfavorable conditions during adolescence led to a decrease in anxiety-like behavior and an increase in exploratory locomotion. Additionally, aggressive behavior was augmented in animals that experienced social adversity. Concerning genotype, homozygous 5-HTT knockout mice were more anxious and less aggressive than heterozygous 5-HTT knockout and wildtype mice. In summary, adolescence is clearly an important phase in which anxiety-like and aggressive behavior can be shaped. Furthermore, it seems that having to cope with challenge during adolescence instead of experiencing throughout beneficial social conditions leads to reduced levels of anxiety-like behavior.